Study on Resistance of Stepped Hull Fitted With Interceptor Plate - Malek, Muhamad Asyraf bin Abdul; Koto, J. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
The application of appendages or trim control mechanisms such as the interceptor plate, stern flap and trim tabs have been widely used in recent years most notably on high speed planning hulls including stepped hulls. With the popular use of stepped hulls in the current market, it is of upmost importance to investigate and predict the resistance of these hulls in order elongate and diversify the lifespan and function of the planning hull. It is also important in a sense to increase the effectiveness of the hulls during operation at various speeds. Eventhough the use of interceptor plates has been catching up in recent years, there had been only a handful of studies investigating the impact of interceptors on the performance of planning hulls. In the present study, a scaled down design of a bare hull used by the Royal Malaysian Customs is used. The bare hull design will be analysed in the CFD software COMSOL Multiphysics with various speeds ranging from 0 to 35.9 m/s. The results that are going to be analysed and discussed later are the total resistance and the pressure contours around the hull. Next, a stepped hull design is analysed using step height of 50 mm to 80 mm. Finally, the optimum step height will be used to be fitted with various interceptor plate height of 18 mm, 22 mm, 26 mm and 30 mm. The effect of appendage, which is the interceptor on the performance of the hull will be analysed and compared to other hull configurations. Based on literature reviews and past studies, it is found that the interceptor plates are able to reduce the total resistance by 15% to 19%. However certain parameters were not taken into account for this study, including the trim angle which is assumed to be zero for all cases. This may cause a slight error in the results, but is deemed allowable for academic purposes.